The Effectiveness of Progressive and Traditional Coaching Strategies to Improve Sprint and Jump Performance Across Varying Levels of Maturation within a General Youth Population - Regan Standing; Peter Maulder (MDPI AG, 2019)
Literature pertaining to youth development has identified the importance of understanding the physical, intellectual and emotional needs of adolescents prior to, during, and after their peak height velocity (PHV) period. The purpose of this study was to compare the use of a ‘traditional’ and ‘progressive’ coaching style to train a general male youth population to improve sprint and jump performances whilst assessing enjoyment to comment on long-term application. Maximal sprint times, sprint kinematics, unilateral jump distances and repetitive tuck jump scores were measured alongside anthropometric variables to characterise performance. The results revealed significant (p < 0.05) pre/post differences in anthropometric variables across all maturation groups, and each of the maturational levels displayed a tendency to favor a particular coaching or control condition. Pre-PHV groups responded most effectively to the progressive style of coaching, displaying improvements in horizontal jump performances, and −0.7% to −2.7% improvements in all sprint times, despite also showing the largest increase in tuck jump scores (25.8%). The circa-PHV group produced their greatest improvements in the traditional intervention, as displayed through significant improvements (p < 0.05) in 20-m sprint times and dominant-leg horizontal jump performance, whilst also revealing the greatest deterioration in tuck jump scores (14.2%). Post-PHV displayed the greatest improvements in the control setting, suggesting that the natural benefits gained through adolescent development were greater than the influence of the training interventions. In conclusion, the results suggest that matching coaching strategies and delivery techniques to the period of biological maturation may have implications for both performance and athlete safety.